Plasmodium falciparum malaria occurring four years after leaving an endemic area. Issue 2 (3rd March 2016) - Vantomme, B.; Van Acker, J.; Rogge, S.; Ommeslag, D.; Donck, J.; Callens, S.
Abstract : We present a case of a 52-year-old woman of Ghanaian origin who developed Plasmodium falciparum malaria 4 years after leaving Africa. She had not returned to an endemic area since. We hypothesize several possible scenarios to explain this infection, of which we believe recrudescence of P. falciparum is the most plausible. This occurred most likely as a consequence of waning immunity several years after leaving a high–transmission area. She recovered after a 3-day treatment with atovaquone/proguanil.